PENGGUNAAN KUNYIT DALAM AIR MINUM TERHADAP PENAMPILAN PRODUKSI PUYUH - Toana, Nuun Marfuah (FAPETKAN UNTAD, 2017)
Turmeric is a type of root that is easy to obtain, contains chemical compounds that have physiological activities, namely essential oils (containing sesquiterpenic alcohol compounds, temuron and zingberen) as well as curcuminoids (containing curcumin and yellow which include desmotoxicurcumin and bidesmetoxicurcumin compounds). This study aimed to determine the use of turmeric level in drinking water on the performance of quail during the production period, in terms of ration consumption, egg production and ration conversion of quails. This research has been carried out in Petobo Village, South Palu Subdistrict, on March 1 to April 15, 2017. This study used 200 female 12-week-old quail, 10 quails were placed in each cage unit. This study used a Completely Randomized Design (CRD), consisting of 4 treatments with 5 replications. The treatments tried are as follows: R0 = Without using turmeric flour in drinking water; R1 = 1 gram of turmeric flour in 1000 ml of drinking water; R2 = 2 grams of turmeric flour in 1000 ml of drinking water; R3 = 3 grams of turmeric flour in 1000 ml of drinking water. The results of the variance analysis showed that the addition of turmeric flour in quail drinking water had no significant effect (P> 0.05) on ration consumption, however a very significant effect (P <0.01) on quail egg production and ration conversion. The conclusion of this study is the use of turmeric flour in drinking water increases egg production and decreases ration conversion.Keyword: Quail, Turmeric, Production Performance